Hyper-fast NMR imaging - Harvey, P. R. (1991)
The work presented in this thesis was carried out in the Physics Department at the University of Nottingham between October 1988 and October 1991. It is the original work of the author except where indicated by reference. This thesis describes the continuation of the development of Echo Volumar Imaging (EVI) to facilitate snapshot imaging of a volume within the human body. Variants of the technique which have also been investigated include a spin echo version, SE-EVI, and a zoomed version ZEVI. All formats acquired data in a modulus fashion in times ranging from 64 ms to 120 ms. Hardware limitations have restricted the image matrix size to 64 x 32 x 8 voxels and prompted the employment of more efficient gradient driver circuitry. A multi-mode resonant gradient circuit is described for use in both Echo Planar Imaging (EPI) and EVI. The circuit behaves in an overall resonant manner but at a fixed number of discrete frequencies. By choosing the number of resonant modes, the circuit can be used to generate approximations to a square wave or trapezoidal waveform. Because of the energy conserving nature of the circuit design much faster current rise times can be achieved with a given amplifier and gradient coil. The multi-mode gradient driver circuit was utilized both for planar imaging and to investigate the effect of rapidly modulated magnetic fields on the human body. A simple neural stimulation model is used to evaluate the stimulation threshold current density for a variety of magnetically induced waveforms and for sinusoidal stimulation as a function of frequency. Experimental results correlate well with the model showing that for short times, contrary to the widely held view, neural stimulation is independent of the magnetic field switching rate dB / dt, but depends on the final magnetic field value.